Curriculum Changes in Indonesia: Implementation and its Challenges in Religious Institutions - Laila, ST. Noer Farida; Mufarokah, Anissatul; Anwar, Heru Saiful; Mudhofar, Alwi (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
The rapid transformation of Indonesia's national curriculum from content-based to competency-based frameworks reflects broader global educational trends aimed at fostering interdisciplinary skills and adaptability. However, this transition presents unique challenges for pesantren-based madrasahs, traditional Islamic educational institutions that balance religious education with national academic standards. This study addresses the gap in research on how madrasahs respond to national curriculum changes, focusing on the implementation and challenges faced by Madrasah Tsanawiyah and Madrasah Aliyah Pondok Pesantren Al-Mawaddah in Ponorogo. Adopting a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. Key informants were purposively selected. They included religious leaders (kyai), teachers, alums, and students. Data analysis followed an interactive model consisting of three stages: data condensation, data display, and conclusion drawing and verification. The findings reveal that while madrasahs implement the national curriculum incrementally, aligning it with traditional Islamic education, they face significant challenges, including increased learning loads, overlapping materials, limited teaching hours, and the dual burden of meeting both national and pesantren-specific evaluation standards. These challenges highlight the tension between maintaining traditional values and adapting to modern educational demands. The study underscores the importance of collaborative policymaking in developing flexible curriculum frameworks and targeted teacher training programs, enabling educators to navigate these complexities. By fostering a process-oriented curriculum that integrates Islamic and general education, pesantren-based madrasahs can better equip graduates with modern competencies while preserving their unique cultural and spiritual identity